Haploinsufficiency of A20 in a Chinese child caused by loss-of-function mutations in TNFAIP3: A case report and review of the literature - Liu, Jing; Lin, Yuese; Li, Xuandi; Ba, Hongjun; He, Xiufang; Peng, Huimin; Li, Shujuan; Zhu, Ling (Frontiers in Pediatrics, 2023)
Case Presentation A 3-year-and-6-month-old child was reported to have recurrent high fever with generalized lymph node enlargement and significant elevation of inflammatory markers such as C-reactive protein and procalcitonin in tests. Later, whole exome sequencing determined that the child's disease was haploinsufficiency of A20 (HA20). Results After immunosuppressive therapy, the child's symptoms improved significantly, and the inflammatory markers dropped to the normal range. Conclusion Because of the characteristics of HA20, this disease is often underdiagnosed and misdiagnosed in clinical practice. By reporting this case of HA20 in a child, we hope to increase the awareness of this disease in the clinic.